Checking rural migration through enhancing farmers income and improving their living conditions - Ali, Nawab (Indian Farming, 2018)
To summarize, it may be said that follow an integrated and intensive farming system to have higher and sustainable agricultural and livestock production and productivity; process the produces in the production catchment to minimize post-harvest losses and get better quality fresh and processed products for consumers; have an economic utilization of agricultural residues, wastes and processing by-products for feed and/ or compost to enhance animal health and soil fertility for better productivity; do the marketing of fresh and value-added products through designated cooperative bulk and/or retail markets with minimum possible number of middlemen/ intermediaries; have more employment for rural men and women and thereby more income to farmers/producers of raw materials. All these when planned and implemented successfully, the rural/ urban gap in prosperity and living comforts would be minimized and people may start reverse migration from urban to rural areas in search of better food, environment, health, happiness and longevity.